Barriers to the Diagnosis and Treatment of Migraine: Effects of Sex, Income, and Headache Features. Issue 1 (18th October 2012) - Lipton, Richard B.; Serrano, Daniel; Holland, Starr; Fanning, Kristina M.; Reed, Michael L.; Buse, Dawn C.
<x xml:space="preserve">Abstract</x> Background.— US Headache Consortium Guidelines state that persons with migraine with headache‐related disability should receive certain acute treatments including migraine‐specific and other medications. However, many eligible individuals do not receive these therapies. Individuals with migraine may experience barriers to receiving minimal appropriate care. We aimed to identify barriers to care in a population sample of individuals with episodic migraine. We assessed barriers at 3 levels: medical consultation, diagnosis, and acute pharmacologic therapy use and assessed the contribution of socioeconomic, demographic, and headache‐specific variables to these barriers. Methods.— We identified 3 steps that were minimally necessary to achieve guideline‐defined appropriate acute pharmacologic therapy as: (1) consulting a prescribing health care professional; (2) receiving a migraine diagnosis; and (3) using migraine‐specific or other appropriate acute treatments. We used data from the 2009 American Migraine Prevalence and Prevention study sample to identify persons with episodic migraine with unmet treatment needs, defined by a Migraine Disability Assessment Scale (MIDAS) score corresponding to Grade II (mild), III (moderate), or IV (severe) headache‐related disability. We determined whether these individuals had consulted a health care professional for headache over the previous year, if they ever received a medical diagnosis of migraine from a health care professional, and whether they were currently using appropriate acute treatment for migraine (ie, a triptan, prescription non‐steroidal anti‐inflammatory drug, or an isometheptene‐containing agent). We analyzed several socioeconomic, demographic, and headache‐specific variables to determine if they were related to barriers in any of the 3 defined steps. Results.— Of 775 eligible participants with episodic migraine and headache‐related disability, 45.5% (n = 353/775) had consulted health care professional for headache in the preceding year. Among those individuals, 86.7% (n = 306/353) reported receiving a medical diagnosis of migraine. Among the diagnosed consulters, 66.7% (204/306) currently used acute migraine‐specific treatments. Only 204 (26.3%) individuals successfully completed all 3 steps. Multivariate logistic regression models revealed that the strongest predictors of current consulting for headache were having health insurance {odds ratio (OR) = 1.73 (95% confidence interval [CI], 1.07‐2.79)}, high headache‐related disability (OR = 1.06 [95% CI, 1.0‐1.14] for a 10‐point change in MIDAS score), and a high composite migraine symptom severity score (OR = 1.19 [95% CI, 1.05‐1.36]). Among consulters, diagnosis was much more likely in women than men (OR = 4.25 [95% CI, 1.61‐11.2]) and became increasingly likely with increasing average headache pain severity (OR = 1.44 [95% CI, 1.12‐1.87]) and migraine symptom severity score. Among those who were diagnosed, annual household income was the strongest predictor of currently using guideline‐defined appropriate acute treatment (OR = 1.44 [95% CI, 1.07‐1.93]) followed by a 10‐point change in MIDAS score (OR 1.16 [95% CI, 1.02‐1.35]). Conclusions.— Among persons with migraine in need of medical care (MIDAS Grade II or greater), only one quarter traversed the 3 steps we proposed to be necessary to achieving minimally appropriate care (consulting, diagnosis, and treatment/medication use). Health insurance status was an important predictor of consulting. Among consulters, women were far more likely to be diagnosed than men, suggesting that gender bias in diagnosis may be an important barrier for men. There were economic barriers related to use of appropriate prescription medications. Public health efforts should focus on improving consultation rates, particularly in the uninsured and diagnostic rates particularly in males with migraine.